Dr. Todd Lefkowitz — Deep Plane Facelift — Columbia - Lefkowitz, Todd (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Todd Lefkowitz, practicing in Columbia, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002970; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; columbia